Incidence of Acute, Progressive, and Delayed Proximal Junctional Kyphosis Over an 8-Year Period in Adult Spinal Deformity Patients. (16th November 2020) - Segreto, Frank A; Passias, Peter G; Lafage, Renaud; Lafage, Virginie; Smith, Justin S; Line, Breton G; Mundis, Gregory M; Bortz, Cole A; Stekas, Nicholas D; Horn, Samantha R; Diebo, Bassel G; Brown, Avery E; et al.
Graphical Abstract: